4 - Migrations, identité et construction étatique au Sahel nigérien : l’expérience des populations du Damargu précolonial (République du Niger) - Malam Issa Mahaman, (Afrika Zamani, 2022)
Located at the crossroads, located between Borno and Hausa land, in the south and Ayar, Touareg country, in the north, Damargu welcomed, from the fifteenth to the nineteenth century, a large population movement because of its various opportunities namely a strategic position on touareg caravan route and the abundance of hunting, agricultural and pastoral lands. The waves of migrants were led by groups of hunters (Baka in Hausa, Kandira in Dagra) coming from the South, whose migrations took place at the same time with those of Kel Tamajaq pastoralits (touareg) coming from the Sahara. All these groups were experts in the manipulation of weapons; skills which gave them a leading position in a region that was open to all types of incursions and disturbances. The process of the migrations stabilisation and the magement of natural resources led the migrants to establish many forms of exchanges and military partnership for the protection of their new country. These relations carried out social transformations and collective identity consciousness.